Cessation of fluoxetine treatment increases alcohol seeking during relapse and dysregulates endocannabinoid and glutamatergic signaling in the central amygdala. (24th July 2019) - Suárez, Juan; Khom, Sophia; Alén, Francisco; Natividad, Luis A.; Varodayan, Florence P.; Patel, Reesha R.; Kirson, Dean; Arco, Rocío; Ballesta, Antonio; Bajo, Michal; Rubio, Leticia; Martin‐Fardon, Rémi; et al.
Abstract: Administration of selective serotonin reuptake inhibitors (SSRIs), typically used as antidepressants, induces long‐lasting behavioral changes associated with alcohol use disorder (AUD). However, the contribution of SSRI (fluoxetine)‐induced alterations in neurobiological processes underlying alcohol relapse such as endocannabinoid and glutamate signaling in the central amygdala (CeA) remains largely unknown. We utilized an integrative approach to study the effects of repeated fluoxetine administration during abstinence on ethanol drinking. Gene expression and biochemical and electrophysiological studies explored the hypothesis that dysregulation in glutamatergic and endocannabinoid mechanisms in the CeA underlie the susceptibility to alcohol relapse. Cessation of daily treatment with fluoxetine (10 mg/kg) during abstinence resulted in a marked increase in ethanol seeking during re‐exposure periods. The increase in ethanol self‐administration was associated with (a) reductions in levels of the endocannabinoids N ‐arachidonoylethanolomine and 2‐arachidonoylglycerol in the CeA, (b) increased amygdalar gene expression of cannabinoid type‐1 receptor ( CB1 ), N ‐acyl phosphatidylethanolamine phospholipase D ( Nape‐pld ), fatty acid amid hydrolase ( Faah ), (c) decreased amygdalar gene expression of ionotropic AMPA ( GluA2 and GluA4 ) and metabotropic ( mGlu3 ) glutamate receptors, and (d) increased glutamatergic receptor function. Overall, our data suggest that the administration of the antidepressant fluoxetine during abstinence dysregulates endocannabinoid signaling and glutamatergic receptor function in the amygdala, facts that likely facilitate alcohol drinking behavior during relapse. Abstract : We demonstrate that treatment with fluoxetine during abstinence resulted in a marked increase in ethanol seeking during re‐exposure. We unveiled neuroadaptations in glutamatergic and endocannabinoid signaling that are associated with fluoxetine‐enhanced ethanol intake. Specifically, we report reductions in levels of endogenous cannabinoids in the central amygdala as well as increased amygdalar gene expression of enzymes related to endocannabinoid signaling system. We also report decreased amygdalar gene expression of several glutamatergic receptor subunits and evidence of increased postsynaptic glutamatergic receptor function.